Improvement of continuous ethanol fermentation from sweet sorghum juice by Saccharomyces cerevisiae using stirred tank bioreactor coupling with plug flow bioreactor - Naulchan Khongsay" (Science Faculty of Chiang Mai University, 2019)
The continuous ethanol production from sweet sorghum juice in a continuous stirred tank bioreactor (STR) and a combined bioreactor was compared. The combined bioreactor comprised an STR and three tubular (plug flow) bioreactors (TB) in series with a total working volume of 3320 ml. The fermentation was carried out at 30°C by Saccharomyces cerevisiae NP 01. The sweet sorghum juice containing 250 g l-1 of total sugar was introduced into the systems at total dilution rates (D) of 0.007, 0.02 and 0.04 h-1. Our results clearly show that the degree of ethanol production depends on the residence time of the fermentation broth in the system. In the STR system at D = 0.007 h-1, the ethanol concentration (P), yield (YP/S) and productivity (QP) were 67.28 ± 0.37 g l-1, 0.52 ± 0.01 g g-1 and 0.47 ± 0.00 g l-1 h-1, respectively. Using the combined bioreactor (CSTR + TB) could improve ethanol production efficiency. The sugar consumption and ethanol production of the combined bioreactor system were markedly higher than those of the STR system. The highest P value (106.01 ± 0.47 g l-1) was obtained when using the combined system at D 0.007 h-1; and under this condition, the YP/S and QP values were 0.50 ± 0.01 g g-1 and 0.76 ± 0.02 g l-1 h-1, respectively.